A strategy to home-in on polygenes influencing susceptibility to anxiety - Gray, J; Flint, J; Dawson, G; Fulker, D (1999)
Genetic influences on susceptibility to neurotic disorders appear to consist of additive polygenes, with collective heritability of 30-50 per cent, determining comorbidity between specific disorders rather than the latter directly. Such susceptibility can be measured by questionnaire, e.g. the Eysenck Neuroticism (N) scale. N scores show a normally distributed variation across the population, with elevated values but no step change in clinical groups. Recent developments in allying the methods of statistical and molecular genetics open the way 60 the location and eventual cloning of polygenes underlying such quantitative traits. We have recently (Flint ct al., 1995, Science, 268, 1432-1435) applied these methods to a population of F-2 mice derived from two inbred strains selectively bred to display extremes on a putative rodent homologue of human Neuroticism (emotionality), identifying three quantitative trait loci (QTLs) showing pleiotropic association with several different behavioural trait markers and collectively accounting for all the additive heritable variance of the trait. We aim to take this result further as follows. (1) Studies of F-2 rats will determine whether QTLs for emotionality in this species are syntenous to those in the mouse. (2) Studies of sib-pairs showing concordance versus discordance for extreme N scores will locate human QTLs for Neuroticism and establish whether they are syntenous with rodent QTLs for emotionality. (3) If rodent-human synteny is established, it will be feasible in principle to clone the genes and determine their function in rodents, although in practice this remains a difficult problem. Copyright (C) 1999 John Wiley and Sons, Ltd.